2017
DOI: 10.1515/botcro-2016-0042
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of microsatellite markers for salt stress in two contrasting maize parental lines and their RIL population

Abstract: -Salt stress considerably hinders the growth and productivity of maize (Zea mays L.). Identifi cation of salt tolerant genotypes and integration of alternative molecular markers have important roles in enhancing breeding processes. In this study, 3308 maize expressed sequence tags (ESTs) from salt stress-related libraries were assembled to mine repetitive sequences for development of applicable markers. In this core EST data, 208 simple and 18 non-simple repetitive regions were detected in 312 contigs and 1121… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(33 reference statements)
1
1
0
1
Order By: Relevance
“…One hundred eighty SSR primers were used to screen two parental lines BTM4 and BTM6 out of which 16 primers (8.89%) were found to be polymorphic among parents. The extent of polymorphism observed in the present study was lower and found similar to earlier studies in maize (Yumurtaci et al 2017). Together for all the 16 primers, the homozygous male, homozygous female and heterozygotes were determined for GGG, GCG and CCC groups of inbred Hence, the combination of gametophytic selection and conventional sporophytic selection should be considered as an efficient tool in population improvement programs to achieve higher levels of tolerance to biotic and abiotic stresses relatively in short time.…”
supporting
confidence: 89%
“…One hundred eighty SSR primers were used to screen two parental lines BTM4 and BTM6 out of which 16 primers (8.89%) were found to be polymorphic among parents. The extent of polymorphism observed in the present study was lower and found similar to earlier studies in maize (Yumurtaci et al 2017). Together for all the 16 primers, the homozygous male, homozygous female and heterozygotes were determined for GGG, GCG and CCC groups of inbred Hence, the combination of gametophytic selection and conventional sporophytic selection should be considered as an efficient tool in population improvement programs to achieve higher levels of tolerance to biotic and abiotic stresses relatively in short time.…”
supporting
confidence: 89%
“…Tabel 1 menunjukkan bahwa salinitas menurunkan kemampuan berkecambah pada semua genotipe. Hasil tersebut sejalan dengan penelitian sebelumnya (Carpici et al, 2009;Sukma et al, 2018). Penurunan kemampuan perkecambahan juga terjadi pada tanaman sorghum (Almodares et al, 2007) dan kedelai (Blanco et al, 2007) Author(s): Kelik Perdana Windra Sukma; Qurrotul Aini __________________________________________ Pada air yang tidak mengandung garam, biji dapat berkecambah dengan baik karena proses imbibisi berjalan dengan baik.…”
Section: Hasil Dan Pembahasanunclassified
“…Indonesia has shorelines 106 thousand kilometers and land potential 1,06 million hectares [5] It can be planted maize, but the main challenge the high content of salt will decrease productivity. Salinity is one of the main limiting factors that can decrease growth and productivity of maize [6] and many plant species [7] Corn var. Duko and Elos are Madura local corn which has the highest resistance to salinity [8].…”
Section: Introductionmentioning
confidence: 99%